Anodic oxidation of Cr3+ ions in a chromium electroplating bath on Pt and composite TiO x/PtO y - Kasian, O. I.; Luk'Yanenko, T. V.; Velichenko, A. B. (Russian Journal of Electrochemistry, 2013)
The effect of various factors (anodic current density, composition of electrolyte, electrode material) on current efficiency of the anodic reaction of formation of Cr(VI) ions is established on Pt and composite TiO x/PtO y under electrolysis of solutions containing Cr 3+ ions. It is shown that the current efficiency values of Cr(VI) on TiO x/PtO y decrease at an increase in the active layer thickness and increase in the electrode treatment temperature. It is found that the major part of Cr(VI) compounds formed on the anode is reduced on the cathode and as a result of homogeneous chemical reactions in the bulk of electrolyte. © 2013 Pleiades Publishing, Ltd.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Anodic oxidation; Cr; Electrocatalysis; TiO